A critical policy analysis of Texas' Closing the Gaps 2015 - Katherine Cumings Mansfield; Stefani Leigh Thachik (Arizona State University, 2016)
This critical policy analysis uses critical race theory to provide a counter narrative to the P-16 initiative in Texas known as Closing the Gaps 2015. Findings indicate that while these reforms aim to increase educational access and achievement for people of color, they fall short of addressing systemic inequities such as enduring segregation and unconstitutional school finance policy. Using Texas as a case study illumines the ways the growing number of P-16 councils throughout the US might adapt and improve policy development and implementation to more adequately address educational inequities across racial, ethnic, and linguistic groups. The article closes with recommendations for Texas' reiteration of Closing the Gaps 2015, titled 60x30TX, currently in revision to guide state education goals in 2016-2030.